Reimagining Physics Education for the 21st Century: A Socio‑Technical Perspective on Curriculum Reform and Industrial Relevance - Mor, Bhupendra (Schrödinger: Journal of Physics Education, 2025)
Purpose of the study: This study aims to design, implement, and evaluate a holistic, modular physics curriculum to address the mismatch between traditional physics education and modern socio-technical demands. The framework integrates foundational rigor with industrial relevance, interdisciplinary agility, and mandatory experiential learning to produce innovation-ready, ethically responsible graduates.Methodology: A longitudinal, single-group, pre-test/post-test quasi-experimental design was used over 12 months with 85 undergraduates. Grounded in Socio-Technical Systems theory, this mixed-methods study used the Purdue Visualization of Rotations Test, industry co-developed surveys, the CATME tool, and an adapted PLIC instrument. Data analysis was conducted using SPSS version 28.Main Findings: The framework yielded significant gains (p < 0.01). Students showed a 22% improvement in spatial reasoning and a 35% increase in industry-aligned competence. Core course failure rates dropped by 50%. Employers reported a 28% reduction in onboarding time. Capstone projects resulted in nine patent-pending prototypes. Ethical-decision scores and interdisciplinary collaboration indices increased by 18% and 25%, respectively.Novelty/Originality of this study: This study is the first to operationalize Socio-Technical Systems theory into a coherent physics curriculum. It uniquely integrates modular stackable micro-credentials, compulsory industry immersion, AR-enabled laboratories, and ethics-driven design challenges within a single framework, providing an actionable, evidence-based roadmap for creating future-ready physicists.